Headspace analysis of aroma compounds using porous adsorbents - Misharina, Tamara (Publishing House of Lviv Polytechnic National University, 2011)
A novel procedure is developed for the quantitative determination of volatile compounds in the vapour phase over samples. Substances were extracted and preconcentrated from the headspace on porous polymer adsorbents under the conditions of thermodynamic equilibrium, followed by back extraction from the adsorbent using organic solvents. The final monitoring was performed by capillary gas chromatography with an internal standard. The influence of adsorption time and the concentration of substances in an aqueous solution on the degree of extraction were also studied; linear correlations between the quantities of substances in the gas and aqueous phases were found. The method was used for the determination of volatile substances in the gas phase over liquid and solid matrixes of different composition. Розроблена нова методика кількісного визначення летких сполук у паровій фазі над зразками. Речовини були екстраговані і попередньо сконцентровані з парової фази полімерних пористих адсорбентів за умов термодинамічної рівноваги, з подальшим їх екстрагуванням з адсорбентів за допомогою органічних розчинників. Залишковий контроль був проведений з використанням капілярної газової хроматографії та застосуванням внутрішнього стандарту. Вивчено вплив тривалості адсорбції та концентрації речовин у водному розчині на ступінь вилучення і знайдено лінійні кореляції між кількістю речовини в газовій та водній фазах. Запропоновано використовувати такий метод для визначення летких речовин в газовій фазі над рідкими та твердими матрицями різного складу.
Aналіз парової фази ароматичних сполук з використанням пористих адсорбентів
Keywords: adsorbent; headspace analysis; quantitative determination; volatile compounds; composition; адсорбент; аналіз парової фази; кількісне визначення; леткі сполуки; композиція